Viewpoint of operating room nurses about factors associated with the occupational burnout: A qualitative study - Teymoori, Esmaeil; Zareiyan, Armin; Babajani-Vafsi, Saeed; Laripour, Reza (Frontiers in Psychology, 2022)
Background: Occupational burnout is a mental health problem that among nurses may lead not only to physical and psychological complications, but also to a decrease in the quality of patient care. Considering the stressful nature of surgery, operating room nurses may be at a greater risk. Therefore, the present study aimed to identifying factors associated with the occupational burnout from the perspective of operating room nurses. Methods: This qualitative study was conducted in Iran in 2021 using conventional content analysis. Sampling was performed using purposeful sampling method with maximum variation. In order to collect data, individual, semi-structured interviews were performed with 18 operating room nurses. Interviews continued until data saturation. Data were recorded, transcribed and analyzed using steps proposed by Graneheim & Lundman. Data management was performed using MAXQDA-2020 software. Four criteria provided by Guba & Lincoln were used to improve the study’s trustworthiness and rigor. Results: A main theme, 4 categories and 15 subcategories were extracted from the data. The main theme is "gradual burnout due to job tension " and categories and subcategories include "organizational factors (manager incompetence, organizational indifference, ambiguity in organizational role, organizational inconsistency), interpersonal factors (surgeon aggression, surgeon authoritarianism, surgeon failure to manage stress, unprofessional behavior of nurses), Occupational nature factors (psychological factors and occupational hazards) as well as individual factors (occupational attitude, unprofessional behavior, emotional involvement, demographic factors, physical factors). Conclusion: Numerous factors associated with burnout in operating room nurses, which may put the personnel under more pressure. According to these factors, nursing managers and operating room nurses can consider effective strategies to prevent or coping with burnout.